America writes its history, 1650/1850 : the formation of a national narrative - Pfister, Jude M. (McFarland & Company, Inc., Publishers, 2014)
By turns irreverent, sympathetic and amusing, America Writes Its History, 1650-1850 adds to the public discourse on national identity as advanced through the written word. Highlighting the contributions of American writers who focused on history, the author shows that for nearly 200 years writers struggled to reflect, or influence, the public perception of America by Americans. This book is an introduction to the development of history as a written art form, and an academic discipline, during America's most crucial and impressionable period. America Writes Its History, 1650-1850 takes the read.